Pacemaker generator replacement as a key to the puzzle of dyspnoea in a community dwelling centenarian. Issue 11 (23rd November 2020) - Schmidt, Tyler; Harmon, David; Pagali, Sandeep
Abstract : A 104-year-old woman presented with dyspnoea. Workup revealed normal troponins, elevated D-dimer at 2285 with subsequent chest CT angiogram negative for pulmonary embolism. NT-pro BNP elevated to 5208 pg/mL. Chest X-ray revealed mild cardiac enlargement with bilateral pleural effusions. ECG revealed accelerated junctional rhythm. The initial plan was to obtain transthoracic echocardiogram and start diuresis for presumed heart failure. Given her specific cardiac history, pacemaker interrogation was ordered which revealed her pacemaker mode changed from DDDR to VVI. She underwent pacemaker battery exchange with complete resolution in her symptoms and ability to return to prior functional status. Overall, dyspnoea in centenarians could be multifactorial. Pacemaker elective replacement mode secondary to end of life battery can present as non-specific cardio respiratory symptoms. As the pacemaker population ages to the survival beyond the battery life, pacemaker aetiology behind heart failure symptoms needs to be highly considered by medical providers.